Ismailism and Islam in modern South Asia community and identity in the age of religious internationals - Mukherjee, Soumen (Cambridge University Press, 2017)
"Explores the evolution of a Shia Ismaili identity in modern South Asia and traces the genealogies of conceptual categories and institutions that conditioned the historical process" --Provided by publisher.